2020
DOI: 10.1002/saj2.20125
|View full text |Cite
|
Sign up to set email alerts
|

Predicting hysteresis loops of the soil water characteristic curve from initial drying

Abstract: The soil water characteristic curve (SWCC) is an important tool in soil science and geotechnical applications. Most previous studies on SWCCs are limited to one to three drying-wetting cycles, mainly because SWCC measurement is complex and time-consuming. The numerous models that have been proposed to predict hysteresis in SWCCs. In this paper, a novel simplified equation is proposed based on the van Genuchten model, whereby SWCC hysteresis can be easily predicted from the initial drying SWCC. The theory for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“… Wen et al (2020b) showed that the water retention capacity of silt and clay decreased with increasing number of drying-wetting cycles. Zhao et al (2020) measured SWCCs during wetting and drying using a pressure plate instrument in multistep outflow experiments and proposed a simplified equation for the main wetting and drying curves, based on the inkbottle effect and entrapped air effects. Wen et al (2021) pointed out that the void ratio of soil is affected by its shrinkage behavior, and thus affects the SWCC.…”
Section: Introductionmentioning
confidence: 99%
“… Wen et al (2020b) showed that the water retention capacity of silt and clay decreased with increasing number of drying-wetting cycles. Zhao et al (2020) measured SWCCs during wetting and drying using a pressure plate instrument in multistep outflow experiments and proposed a simplified equation for the main wetting and drying curves, based on the inkbottle effect and entrapped air effects. Wen et al (2021) pointed out that the void ratio of soil is affected by its shrinkage behavior, and thus affects the SWCC.…”
Section: Introductionmentioning
confidence: 99%
“…The SWRC is the basis for the estimation of hydraulic parameters, which are the required inputs for simulations of water flow and solute transport (Smagin, 2011;Xing et al, 2018bXing et al, , 2021. In many previous researches, the SWRC was widely adopted to evaluate the size and distribution of soil pores and soil water availability (Mengistu et al, 2019;Neyshaburi et al, 2015); moreover, among the SWRC models, the van-Genuchten model (van Genuchten, 1980) and the Brooks-Corey model (Brooks and Corey, 1964) were also widely applied to determine soil hydraulic conductivity and soil water diffusivity (Latorre and Moret-Fern andez, 2019;Ma et al, 2016;Peña-Sancho et al, 2017;Wen et al, 2019;Zhao et al, 2020). Another exponential model of the hydraulic conductivity-soil suction relationship, the Gardner-Russo model (Gardner, 1958;Russo, 1988), has not yet been widely focused or utilized for hydraulic parameter derivation in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…e CDG at the top of the tunnel will induce the floating deformation in a loading-unloading process; therefore, it is necessary to obtain the CDG soil properties for construction guidance [6][7][8][9][10][11][12][13][14][15][16]. Lan et al [3] statistically analyzed the differences in composition, stress, and strain characteristics of CDG with different degrees of weathering in southern China.…”
Section: Introductionmentioning
confidence: 99%